1988
DOI: 10.1111/j.1528-1157.1988.tb03741.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex Partial Seizures of Hippocampal and Amygdalar Origin

Abstract: We studied the first clinical manifestations of 72 complex partial seizures (CPS) in 17 drug-resistant patients. CPS were indicated to be of hippocampal-amygdalar origin by scalp and depth EEG. We asked: (a) Do all CPS of hippocampal-amygdalar origin start with an initial motionless stare and/or oroalimentary automatisms? (b) If not, what other clinical manifestations appear at onset of the CPS? Results showed that approximately 39% of CPS begin with motionless staring, 25% with nonfocal discrete movements, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Taken together with the less frequent presence of staring and OAs, this previously unreported finding suggests that BTLE patients may have different brain networks from those of UTLE patients, possibly leading to more frequent neocortical than mesial seizure onset and discharge propagation [33][34][35].…”
Section: Discussionmentioning
confidence: 90%
“…Taken together with the less frequent presence of staring and OAs, this previously unreported finding suggests that BTLE patients may have different brain networks from those of UTLE patients, possibly leading to more frequent neocortical than mesial seizure onset and discharge propagation [33][34][35].…”
Section: Discussionmentioning
confidence: 90%
“…The authors identified three clinical phases during most of the 76 seizures recorded, beginning with a motionless stare early in the event, followed by stereotypical movements, and with loss of consciousness later in the seizure (Escueta et al, 1977). Another study of 72 hippocampal or amygdalar seizures found that motionless staring or oroalimentary automatisms were the first behavioral manifestations during the majority of events (60%), with fewer seizures beginning with nonfocal discrete movements, perseverative stereotyped automatisms, or vocalizations (Maldonado et al, 1988). In general, whereas automatisms and other behavioral manifestations usually emerge early in a complex-partial seizure, while responsiveness may remain intact, consciousness in TLE is most profoundly affected late in the seizure and during the postictal period (Blumenfeld and Taylor, 2003).…”
Section: Behavioral Semiology Of Temporal Lobe Seizuresmentioning
confidence: 99%
“…Except for gestural automatism, these were also the most frequently identifi ed phenomena in the present study. These manifestations are also common in adults with mesial temporal lobe epilepsy 24 . Epigastric phenomenon and fear, although being frequent manifestations in adults 12,25 , present lower incidence among children, maybe due to the diffi culty of the child to report these sensations.…”
Section: Discussionmentioning
confidence: 99%